The Land of Wide: The Vision of Ukrainians towards Tourism Development - Rudnyk, Olena (2011)
Abstract Purpose This research aims to investigate the perceptions and attitudes of residents towards tourism development in the Ukraine. Design/Methodology/Approach • Literature review. • Ap & Crompton (1998) Index. • Questionnaire posed to the residents of the Ukraine. • Interviews with two travel agency managers, and one foreigner. • A thematic data analysis. Findings The results have established a lack of policy in regard to environmental protection, including a poor water resource infrastructure alongside a lack of awareness in this regard. Moreover, corruption is widely common attributed to mass tourism. Notably, there have been various UN attempts towards raising public awareness, and a recent increase in direct foreign investments, despite the lack of adequate legalisation and investment policy protection. Furthermore, low personal wages run alongside high company income, reflecting negatively in terms of the significance of tourism development. This comes as a result of a seeming lack of cooperation between the Ministry of Tourism and the private sector. A strong belief amongst Ukrainian culture seems not to be influenced by tourism development; this contributes substantially to the recreation of the hidden culture as a result of tourism development. The crime rate has decreased as a result of tourism development; however, the birth of marriage tourism is considered to cause social conflict, racism and anti-foreigner attitudes. Rural areas are overlooked in terms of infrastructure alongside increasingly ecotourism activities. Practical Implications The results have provided insight into the consideration that the Ukrainian government and Ukrainians need to gain understanding into the significance of tourism development and its related issues for long-term growth.